Fundamental analysis, low accruals, and the accrual anomaly: Korean evidence. Issue 3 (3rd July 2021) - Kim, Young Jun; Kim, Jung Hoon; Kwon, Sewon; Lee, Su Jeong
ABSTRACT: Prior studies in Korea document that low accrual firms yield extremely low returns, driving away abnormal returns of an accrual-based trading strategy. We examine whether the performance of an accrual-based trading strategy can be improved using fundamental analysis to distinguish financially strong firms ('winners') from financially weak firms ('losers') within low accrual firms. Using Korean data from 1994 to 2018, our findings are summarised as follows. First, applying FSCORE in Piotroski (2000) [Journal of Accounting Research, 38(supplement), 1–41] to distinguish winners from losers within low accrual firms, we find that winners yield much higher future returns than losers. Second, after excluding losers in the low accrual group, the accruals-based hedge portfolio exhibits higher abnormal returns. Lastly, we find that, among low accrual firms, higher FSCORE is associated with less negative accruals, higher future probability, and lower probability of delisting. Overall, our findings imply that the extremely negative accruals (i.e., low accruals) do not signal good fundamentals, although Piotroski (2000) treats the negative sign of accruals as a universally positive signal of future performance. It also implies that investors do not fully incorporate the implications of low accruals for future performance.